Mobile Health Intervensi untuk Peningkatan Perawatan Ibu Hamil di Kota Semarang - Fitria Wulandari; Lenci Aryani (Dian Nuswantoro Semarang, 2018)
Mobile health with its popularity and availability has considerable potential to increase access to health care, especially in improving maternal health. Mobile health-based interventions are used to spread health information because of its availability, cheap and does not require large technological expertise, can be accessed at any time. Previous research has proven that periodic message reminders using cellphones effectively encourage and strengthen healthy behavior. This research is part of a health promotion intervention for pregnant women based on mobile health which aims to evaluate the use of mobile health to promote the health of pregnant women qualitatively.Descriptive qualitative research design with an observational approach from the results of the intervention of pregnant women groups conducted in April - July 2018. A purposive sampling technique, the number of samples 102. Qualitative data analysis in this study.The number of respondents using whatsapp application 102 people, 47% active respondents. Mobile health for effective health promotion (97%) and acceptable. Interesting content (98%) in general assessment of positive content: increasing knowledge of pregnant women (68%). The most questions about the daily care of pregnant women, the response to the intervention: can continue until the respondent gives birth.Mobile health for health promotion of pregnant women is effective and acceptable.